2019
DOI: 10.1074/jbc.ra119.011237
|View full text |Cite
|
Sign up to set email alerts
|

The apparent deglycase activity of DJ-1 results from the conversion of free methylglyoxal present in fast equilibrium with hemithioacetals and hemiaminals

Abstract: Edited by Ruma Banerjee Loss-of-function mutations in the gene encoding human protein DJ-1 cause early onset of Parkinson's disease, suggesting that DJ-1 protects dopaminergic neurons. The molecular mechanisms underlying this neuroprotection are unclear; however, DJ-1 has been suggested to be a GSH-independent glyoxalase that detoxifies methylglyoxal (MGO) by converting it into lactate. It has also been suggested that DJ-1 serves as a deglycase that catalyzes hydrolysis of hemithioacetals and hemiaminals forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
74
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(101 citation statements)
references
References 25 publications
21
74
0
Order By: Relevance
“…In this scenario, DJ-1 has been described to convert MGO and GO in less harmful species, by acting as a glutathione-independent glyoxalase [ [40] , [41] , [42] , [43] , [44] ]. Furthermore, some studies have reported that DJ-1 can deglycate both proteins and nucleic acids upon reaction with MGO [ [45] , [46] , [47] , [48] , [49] , [50] ], though this function has proved contentious by other reports [ 51 , 52 ]. Interestingly, DJ-1 also seems to participate in the preservation of glucose homeostasis, by regulating the glucose levels in the brown adipose tissue [ 53 ] and by modulating the subcellular localization of the glycolytic enzyme hexokinase I [ 32 ].…”
Section: Dj-1: a Multifunctional Protein Against Cellular Stressmentioning
confidence: 99%
“…In this scenario, DJ-1 has been described to convert MGO and GO in less harmful species, by acting as a glutathione-independent glyoxalase [ [40] , [41] , [42] , [43] , [44] ]. Furthermore, some studies have reported that DJ-1 can deglycate both proteins and nucleic acids upon reaction with MGO [ [45] , [46] , [47] , [48] , [49] , [50] ], though this function has proved contentious by other reports [ 51 , 52 ]. Interestingly, DJ-1 also seems to participate in the preservation of glucose homeostasis, by regulating the glucose levels in the brown adipose tissue [ 53 ] and by modulating the subcellular localization of the glycolytic enzyme hexokinase I [ 32 ].…”
Section: Dj-1: a Multifunctional Protein Against Cellular Stressmentioning
confidence: 99%
“…The authors suggested that deglycation constitutes the primary cell-physiological function of DJ-1. However, this concept has been challenged [ 42 , 43 ]. Using the in vitro model system of differentiated SH SY5Y cells, we probed for the potential deglycation properties of the four different DJ-1 variants.…”
Section: Resultsmentioning
confidence: 99%
“…A protective effect of DJ-1 against protein glycation has been shown in yeast, bacteria [ 49 ] and human keratinocytes [ 50 ]. Whether DJ-1 detoxifies free MGO by acting as a glyoxalase [ 12 , 42 , 51 ] or removes adducts formed by MGO on proteins by acting as a deglycase [ 14 , 52 ] is a matter of debate. Here we confirm a C106-dependent protective effect of DJ-1 on protein glycation in neuron-like cells and show that in our cellular system H8 is essential for this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of DJ-1 was shown to increase the levels of glycated DNA and DNA strand breaks [38]. However, the proposed deglycase activity of DJ-1 is not yet commonly accepted, as conflicting observations have been reported [108,109]. If confirmed, it would imply, however, that lack of functional DJ-1 could lead to reduced protection from glycation, increased DNA and protein damage and, hence, premature cellular aging via accumulation of advanced glycation end products (AGEs) [38].…”
Section: Dj-1 and Pathophysiological Implications Of Altered Metabolimentioning
confidence: 99%